Quantitative Studies on the Structure of Zirconium Fluoride Anions in Molten LiF and FLiBe. Issue 1 (18th December 2021) - Liu, Xiyan; Hu, Jingwen; Wang, Chenyang
Abstract: The quantitative distribution of different zirconium fluoride anions in molten LiF and FLiBe mixtures has been investigated by Raman and theoretical calculations. In molten LiF, zirconium fluorides are present in the forms of ZrF6 2− and ZrF7 3− . After correction, the Raman scattering cross sections corresponding to the symmetric stretching vibrational bands were obtained. The ZrF7 3− anion was a dominant species whatever the concentration of ZrF4 between 5 and 30 mol % in LiF melt, even though the content of which presents a decreasing trend from 92.3 to 73.2 mol % with the increase of ZrF4 . Similar specification was identified in FLiBe‐ZrF4, and ZrF6 2− /ZrF7 3− anions were found in equilibrium with free F − ions and beryllium fluoride anions. Detailed deconvolution and calculation were performed on the Raman spectrum measured in the FLiBe melt containing 10 mol % ZrF4 giving a quantitative content of ZrF7 3− 78.1 mol % and ZrF6 2− 21.9 mol %. Abstract : The quantitative distribution of the zirconium fluoride anions in molten LiF and FLiBe mixtures has been investigated by Raman spectroscopy and density functional theory calculation that present in the form of ZrF6 2− and ZrF7 3− . The ZrF7 3− anion was found to be a dominant species in both LiF and FLiBe molten with a certain ZrF4 concentration.